ANALISIS PERLAKUAN AKUNTANSI TERHADAP PENERIMAAN NEGARA BUKAN PAJAK (PNBP) ATAS JASA LAYANAN IPTEK NUKLIR - Sri Agustini (Universitas Pamulang, 2019)
The mechanism for managing PNBP services in BATAN is guided by Law (Law) Number 20 of 2017 concerning PNBP, Government Regulation (PP) Number 29 of 2011 concerning Types and Rates of PNBP Types that Apply to the National Nuclear Energy Agency, Government Regulation (PP) Number 71 of 2010 concerning Government Accounting Standards (SAP), Technical Bulletin of Government Accounting Standards Number 23 concerning Accounting for Non-Tax Revenue Collection, and Regulation of the Minister of Finance of the Republic of Indonesia (PMK-RI) Number 152 / PMK.02 / 2014 concerning Instructions for the Compilation of PNBP of the State Ministries / Institutions implemented by 16 work units in BATAN for 15 types of Nuclear Science and Technology services. In order to meet the needs of the community for goods / services in the nuclear sector, BATAN provides services in the field of nuclear science and technology (science and technology), one of which is carried out through an application system. In line with bureaucratic reforms which have an impact on changes in governance in various fields, the regulation of PNBP. Law Number 20 Year 1997 concerning PNBP only contains PNBP groups and rules in general, and their implementation is regulated in detail through PP. However, the preparation of legislation requires a long time, while the implementation of PNBP must continue to run. In implementing PNBP, BATAN is increasingly demanded to provide services that are fast, easy, practical and transparent. Service customers do not have to come to the intended work unit to complete administration. With online-based administration all communication with customers can be done both ways. This study uses descriptive analysis, showing the largest percentage of PNBP service use in BATAN out of 15 types of Nuclear Science and Technology services in 2017 conducted by the PSTBM Work Unit (99.64%) and the smallest percentage of use by the PTBGN Work Unit (5.88%) (able seen in the results of the discussion on pages 10-14). Keywords: PNBP, Measurement,Acceptance, Use, Nuclear Science and Technology Services.